Expression of Sox4 and Sox11 is regulated by multiple mechanisms during retinal development. - Wegner, Michael; et al. (Febs Letters, 2013)
Sox11 and Sox4 play critical roles in retinal development, during which they display specific and unique expression patterns. The expression of Sox11 and Sox4 is temporally sequential, albeit spatially overlapping in some retinal subtypes. Gain-of-function and loss-of-function analyses suggested that Notch signaling suppresses Sox4 expression in the early developing retina but not during the later period of development. The levels of histone H3-acetylation and H3-lysine 4 tri-methylation at the Sox11 locus declined during development, as did the levels of Sox11. A similar but less marked change was seen for Sox4. For both genes, histone H3-lysine 27 methylation was low during development and increased markedly in the adult. © 2013 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2013.med.IB.LPCIPDBI.expres
Keywords: Development; Histone modification; Notch; Retina; Sox C family transcription factor; Transcriptional regulation